2012
DOI: 10.4103/1463-1741.95134
|View full text |Cite
|
Sign up to set email alerts
|

Early occupational hearing loss of workers in a stone crushing industry: Our experience in a developing country

Abstract: Noise-induced hearing loss (NIHL) is an irreversible sensorineural hearing loss associated with exposure to high levels of excessive noise. This paper aims to assess the prevalence of early NIHL and the awareness of the effects of noise on health among stone crushing industry workers. This was a comparative cross-sectional study in Ghana of 140 workers from the stone crushing industry compared with a control group of 150 health workers. The stone workers and controls were evaluated using a structured questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
4
15
0
Order By: Relevance
“…A total of 281 references were recovered when the described search criteria were applied; after purging the duplicated references and after the application of inclusion/exclusion criteria, it was possible to retrieve 23 studies with available full text[7111214151819202122232425262728293031323334353637] [Table 1], proceeding from MEDLINE ( n =10; 40.00%), Cochrane ( n = 1; 4.00%), ISI Web of Science ( n =2; 8.00%), Scopus ( n =10; 40.00%), and SciELO ( n =2; 8.00%). The concordance between the evaluators about the pertinence of the articles was 100%.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 281 references were recovered when the described search criteria were applied; after purging the duplicated references and after the application of inclusion/exclusion criteria, it was possible to retrieve 23 studies with available full text[7111214151819202122232425262728293031323334353637] [Table 1], proceeding from MEDLINE ( n =10; 40.00%), Cochrane ( n = 1; 4.00%), ISI Web of Science ( n =2; 8.00%), Scopus ( n =10; 40.00%), and SciELO ( n =2; 8.00%). The concordance between the evaluators about the pertinence of the articles was 100%.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] A formal sector enterprise is an enterprise which is either government or privately owned, but is subject to government regulation. Within Ghana, Kitcher et al [8] noted a high prevalence of early NIHL among workers in a formal enterprise of a large-scale stone crushing industry. Boateng and Amedofu [9] also reported NIHL among local saw mill, printing press and corn mill workers.…”
Section: Introductionmentioning
confidence: 98%
“…Fernandes et al also reported a higher NIHL prevalence in the left ears of urban bus drivers. [6] This suggests that lateralization of hearing loss is evident in occupational NIHL. In the present study, we observed higher BERA abnormalities in left ear.…”
Section: Discussionmentioning
confidence: 98%
“…[7,8] To assess hearing loss in most of the previous studies pure tone audiometry (PTA) that may have subjectively biased results and hence interpretation, were used. [5][6][7][8][9] Very few studies have adopted brainstem evoked response audiometry (BERA) to assess hearing loss and auditory pathway affection whether central or peripheral. BERA rules out any subjective recording of hearing threshold.…”
mentioning
confidence: 99%